MANAJEMEN FASILITAS MULTIMEDIA MASJID AR-RAHMAH PERAK SURABAYA - Qisom, Shobikhul (STIDKI Ar Rahmah, Surabaya, 2020)
ABSTRACTThe rapid development of technology is one thing that really needs to be considered. The role of multimedia is very influential for sensory comprehension and attracts the attention and interest of consumers or congregations. The Ar Rahmah Mosque in Surabaya has also utilized multimedia facilities in executing its programs. Good managerial ability with multimedia facilities is also a supporting factor for the Ar Rahmah Mosque that is not technologically illiterate. This study aims to determine how to manage multimedia facilities at the Ar Rahmah Mosque in Surabaya. Primary data collection is obtained through interview method with resource persons who play a direct role in the management of the Ar Rahmah Mosque, while secondary data is obtained through literature study. The data were analyzed descriptively qualitatively. Surabaya Ar Rahmah Mosque has equipped multimedia facilities to support its mosque program. The Ar Rahmah Mosque has also implemented management functions in multimedia facilities, from planning to monitoring functions. However, in its implementation there are still some technical and non-technical obstacles, so it is necessary to evaluate and improve the management system.ABSTRAKPerkembangan teknologi yang begitu pesat merupakan salah satu hal yang sangat perlu diperhatikan. Peran multimedia sangat berpengaruh bagi daya tangkap indera dan menarik perhatian serta minat konsumen atau jama’ah. Masjid Ar Rahmah Surabaya juga telah memanfaatkan fasilitas multimedia dalam mesyi’arkan program-programnya. Kemampuan manajerial yang baik terhadap fasilitas multimedia tersebut juga menjadi faktor pendukung Masjid Ar Rahmah tidak gagap teknologi. Penelitian ini bertujuan untuk mengetahui cara manajemen fasilitas multimedia di Masjid Ar Rahmah Surabaya. Pengumpulan data primer diperoleh melalui metode wawancara dengan narasumber yang berperan langsung dalam manajemen Masjid Ar Rahmah, sedangkan data sekunder diperoleh melalui studi pustaka. Dat-data tersebut dianalisis secara deskriptif kualitatif. Masjid Ar Rahmah Surabaya telah melengkapi fasilitas multimedia untuk menunjang program kemasjidannya. Masjid Ar Rahmah juga telah menerapkan fungsi manajemen terdahap fasilitas multimedia, mulai dari fungsi perencanaan hingga pengawasan. Namun dalam pelaksanaannya masih ditemukan beberapa kendala teknis maupun non teknis, sehingga perlu dilakukan evaluasi dan perbaikan sistem manajemen.